How Many Is Enough? - Challenges of Multinucleated Cell Division in Malaria Parasites - Simon, Caroline S.; Stürmer, Vanessa S.; Guizetti, Julien (Frontiers in Cellular and Infection Microbiology, 2021)
Regulating the number of progeny generated by replicative cell cycles is critical for any organism to best adapt to its environment. Classically, the decision whether to divide further is made after cell division is completed by cytokinesis and can be triggered by intrinsic or extrinsic factors. Contrarily, cell cycles of some species, such as the malaria-causing parasites, go through multinucleated cell stages. Hence, their number of progeny is determined prior to the completion of cell division. This should fundamentally affect how the process is regulated and raises questions about advantages and challenges of multinucleation in eukaryotes. Throughout their life cycle Plasmodium spp. parasites undergo four phases of extensive proliferation, which differ over three orders of magnitude in the amount of daughter cells that are produced by a single progenitor. Even during the asexual blood stage proliferation parasites can produce very variable numbers of progeny within one replicative cycle. Here, we review the few factors that have been shown to affect those numbers. We further provide a comparative quantification of merozoite numbers in several P. knowlesi and P. falciparum parasite strains, and we discuss the general processes that may regulate progeny number in the context of host-parasite interactions. Finally, we provide a perspective of the critical knowledge gaps hindering our understanding of the molecular mechanisms underlying this exciting and atypical mode of parasite multiplication.